Digitally-assisted analog and analog-assisted digital IC design - Jiang, Xicheng, 1968- (Cambridge University Press, 2015)
"Achieve enhanced performance with this guide to cutting-edge techniques for digitally-assisted analog and analog-assisted digital integrated circuit design. Discover how architecture and circuit innovations can deliver improved performance in terms of speed, density, power, and cost. Learn about practical design considerations for high-performance scaled CMOS processes, FinFet devices and architectures, and the implications of FD SOI technology. Get up to speed with established circuit techniques that take advantage of scaled CMOS process technology in analog, digital, RF and SoC designs, including digitally-assisted techniques for data converters, DSP enabled frequency synthesizers, and digital controllers for switching power converters. With detailed descriptions, explanations, and practical advice from leading industry experts, this is an ideal resource for practicing engineers, researchers, and graduate students working in circuit design."--